Evaluación de una entidad financiera usando Camel: el caso de BBVA Perú - Lizarzaburu Bolaños, Edmundo (2022)
The present case study was aimed at analyzing the financial situation of BBVA Peru using the CAMEL methodology. Additionally, a proper valuation was carried out using Comparable Multiples and Discounted Cash Flow methods. The first was to describe the economic environment through a Top-Down methodology: region, country, financial sector, and company. The period of analysis was 2015-2019. The data analyzed belonged to production, industry, and technology. Moreover, the bank operations are presented detailing the income structure, financial products and services, politics, and corporate governance.